Multifunctional Integrated Transparent Film for Efficient Electromagnetic Protection - Wang, Gehuan; Zhao, Yue; Yang, Feng; Zhang, Yi; Zhou, Ming; Ji, Guangbin (Nano-Micro Letters, 2022)
Silver nanowire (Ag NW) has been considered as the promising building block for the fabrication of transparent electromagnetic interference (EMI) shielding films. However, the practical application of Ag NW-based EMI shielding films has been restricted due to the unsatisfactory stability of Ag NW. Herein, we proposed a reduced graphene oxide (rGO) decorated Ag NW film, which realizes a seamless integration of optical transparency, highly efficient EMI shielding, reliable durability and stability. The Ag NW constructs a highly transparent and conductive network, and the rGO provides additional conductive path, showing a superior EMI shielding effectiveness (SE) of 33.62 dB at transmittance of 81.9%. In addition, the top rGO layer enables the hybrid film with reliable durability and chemical stability, which can maintain 96% and 90% EMI SE after 1000 times bending cycles at radius of 2 mm and exposure in air for 80 days. Furthermore, the rGO/Ag NW films also possess fast thermal response and heating stability, making them highly applicable in wearable devices. The synergy of Ag NW and rGO grants the hybrid EMI shielding film multiple desired functions and meanwhile overcomes the shortcomings of Ag NW. This work provides a reference for preparing multifunctional integrated transparent EMI shielding film. Highlights: 1 The reduced graphene oxide (rGO) decorated silver nanowire (Ag NW) films were prepared by spray-coating method. 2 A highly efficient conductive network was constructed by Ag NW and rGO, achieving superior electromagnetic interference shielding effectiveness of 33.62 dB with a high transmittance of 81.9%. 3 The top rGO layer enables the hybrid film with reliable durability, chemical and thermal stabilities.